Development of Gram Stain Scoring System Based on Pro-Inflammatory Cytokines in the Sheep Model for Testing Toxicity of Vaginal Products - Vincent, Kathleen L.; Miller, Aaron L.; Maxwell, Carrie; Richardson-Harman, Nicola; O'Neill, Cynthia; Dawson, Lauren N.; Madsen, Timothy; Walker, Cattlena; Swartz, Glenn; Pyles, Richard B. (Frontiers in Reproductive Health, 2021)
Development of safe, effective products to prevent sexual transmission of HIV remains a priority. Prior to clinical testing, products must undergo strict safety evaluations to avoid mucosal drug toxicity, inflammation, and vaginal microbiome (VMB) shifts. Based on FDA guidance, we designed a study to measure inflammatory markers and VMB changes after intravaginal treatment with products that have been associated with toxicity, with the objective to develop a Gram stain slide scoring system, similar to Nugent scoring, correlated with proinflammatory cytokines in sheep. Nonpregnant Dorset ewes (n=34) were randomized to receive 5mL intravaginal 4%nonoxynol-9 contraceptive gel, positive control (0.2%benzalkonium chloride), placebo control (hydroxethyl cellulose), or no application daily for 10 days, with 11-day post-treatment follow-up. Vaginal swabs were collected for cytokines, VMB, and Gram-stained slides. ELISA analysis of cytokines IL-1β, IL-8, CXCL10 and TNF-α was used to determine inflammatory state of the sample. VMB community types were utilized to create 5 equivalent slide subsets for iterative development of a Gram-stained slide scoring system with comparisons to inflammatory state based on cytokine levels. Digital images of Gram-stained slides were scored based on Gram-staining and morphology of bacteria, presence of sheep epithelial cells, and immune cells. The scoring system was modified in an iterative fashion with weighting based on cytokine categorization of inflamed samples, with 3 of 4 cytokine values above the mean indicating the sample was inflamed. Parameters in the final version of the scoring system included mature epithelial cells, Gram-negative rods, and Gram-positive diplococci indicating normal and immune cells indicating inflammation. The Area Under the Receiver Operator Characteristic Curve (ROC AUC) was 0.725, (ROC AUCs range between 0.5-1.0) with a greater area indicating higher diagnostic ability of a test with a binary outcome: inflamed or normal. The scoring system, derived from advanced VMB and cytokine analyses, provides a validated, practical method for quantification of Gram-stained slides that can be performed in most labs, increasing the potential for standardization. The training plan can assist labs to determine safety of intravaginal products in their sheep studies or the methodological approach can be applied to other animal models where such data are also needed.